Analisis Pengelolaan Sumber Daya Alam Sebagai Sumber Pendapatan Ekonomi Masyarakat Lokal Di Sempadan Sungai Rungan Kota Palangka Raya - Nova Riyanti; Muhammad Riban Satia; Muh Azhari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This research aims to analyze the management of natural resources as a resource as a source of economic income of local communities on the border of the river Rungan Palangka Raya City. As long as this local community relies only on fishery resources, while fishery resources are now difficult to find due to various pollution that occurs. The research approach in this research is a qualitative descriptive that aims to illustrate the complexity and dynamism of natural resources management for the local community's economic income. Data collection In this research researchers use field research techniques that are data collection techniques conducted using researchers plunge directly into the field where the research location is conducted. The data collection techniques used are observations, interviews, documentation, and literature studies. The results showed research conclusions that during this time, the management of potential natural resources available has not been well managed. So that the unmanaged natural resources are not able to provide a permanent source of economic income for local communities on the border of the city of Palangka Raya River. Whereas various potentials can be developed for the source of economic income of local people such as plants and plants that can be cultivated and have local wisdom to be religious tourism that can be a source of economic income of local people. The barriers to natural resource management for the source of economic income of local communities on the boundary of the Rungan River of Palangka Raya City are 1) personal ownership or land tenure, 2)from the institutional and Non-institutional side. 3) No support and utilization of technology in the management of natural resources for the source of economic income of local communities.